Research capacity development in a South African higher education institution through a north-south collaboration - Frantz, Jose M; Leach, Lloyd; Pharaoh, Hamilton; Bassett, Susan; Roman, Nicolette; Smith, Mario; Travill, Andre (South African Journal of Higher Education, 2018)
One of the constraints that prevent institutions in developing countries from engaging in effective and essential research is a lack of research capacity. This study reports on a north-south collaboration between a group of Flemish universities and a higher education institution in South Africa with the specific goal of improving productivity, quality and capacity amongst researchers. A collaborative project with multiple sub-projects was established in 2003, and extended over two consecutive five-year phases. Document analysis was conducted of annual reports, monitoring and evaluation reports, curriculum vitae of participating members, and progress reports of students and supervisors during this time. The findings of this study illustrate the extent to which research capacity objectives can be achieved through a north-south partnership. Members of the collaboration were able to develop intra- and inter-disciplinary partnerships that resulted in maximising the capacity- building efforts, enhancing both individual and institutional research capacity. Keywords: International partnerships; professional development; student development; staff development.